Numerical solution of boundary value problems for stochastic differential equations on the basis of the Gibbs sampler - Sergej M. Prigarin; Gerhard Winkler (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
To solve boundary value problems for linear systems of stochastic differential equations we propose and justify a numerical method based on the Gibbs sampler. In contrast to the technique which yields for linear systems an "exact" numerical solution, the proposed method is simpler to generalize for stochastic partial differential equations and nonlinear systems. Such generalizations are discussed as well.
urn:nbn:de:bvb:19-epub-1707-2
Keywords: 519; Analysis; Stochastischer Prozess; Theorie